APPLICATION OF GROUP COUNSELING WITH BEHAVIOR CONTRAC TECHNIQUES TO REDUCE TRUANT BEHAVIOR IN STUDENTS AT SMK PGRI 1 BANYUWANGI: PENERAPAN KONSELING KELOMPOK DENGAN TEKNIK BEHAVIOR CONTRAC UNTUK MENGURANGI PERILAKU MEMBOLOS PADA SISWA DI SMK PGRI 1 BANYUWANGI - Nila Rahmani; Siti Napisah; Dhalia Soetopo (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
This research examines the effectiveness of behavioral contract techniques to reduce students' ’ruancy behavior at SMK PGRI 1 Banyuwangi. The problems in this research are: (1) What is the description of students' ’ruant behavior at SMK PGRI 1 Banyuwangi? (2) What is the description of the implementation of behavioral contract techniques for students at SMK PGRI 1 Banyuwangi? (3) Can the behavioral contract technique reduce students' truancy habits at SMK PGRI 1 Banyuwangi? The aim of this research is to determine: (1) A description of students' ’ruancy behavior at SMK PGRI 1 Banyuwangi, (2) a description of the implementation of the behavioral contract technique among students at SMK PGRI 1 Banyuwangi (3) The effectiveness of the behavioral contract technique for reducing student truancy behavior at SMK PGRI 1 Banyuwangi. This research is quantitative research with the type of experimental research Single Subject Research. The subjects of this research were five students with the initials RY, EI, DS, DK, and DA. Data collection techniques used observation, interviews and documentation.